Implementation of the jigsaw cooperative learning model to optimize learning outcomes in fundamental volleyball techniques - Irvan Irvan; Peby Gunarto; I Komang Sukarata Adnyana (Sriwijaya Journal of Sport, 2025)
Research Problems: Low mastery of basic volleyball techniques in physical education classes—caused by using conventional learning methods that tend to be passive—is a major problem, requiring the application of innovative and participatory learning models such as the Cooperative Type Jigsaw to maximize student learning outcomes. Research Objectives: This study aims to improve learning outcomes in physical education on basic volleyball techniques—which were previously low due to conventional methods—by applying the Cooperative Jigsaw Learning Model, and the results show that this model is effective in improving students' mastery of the material. Methods: This study used the Classroom Action Research (CAR) method, which was carried out in two cycles. Each cycle consisted of four main stages, namely: action planning, action implementation, observation/evaluation of actions, and reflection on actions. The research subjects were 22 students of Class XI of Muhammadiyah 2 Singaraja High School in the 2024/2025 academic year. Results: The results of this study indicate that there was a significant increase in student learning outcomes, particularly in the basic techniques of underhand and overhand passing in volleyball. This improvement was clear from the increase in the average scores obtained by students during the study. This was supported by an increase in the learning completion rate from 54.54% in Cycle I to 81.81% in Cycle II. Conclusion: The implementation of the Cooperative Type Jigsaw Learning Model has proven to be effective in improving learning outcomes in physical education, particularly in mastering underhand and overhand passing techniques, for students in Grade XI at Muhammadiyah 2 Singaraja High School in the 2024/2025 academic year.